Analisis Modul Ajar Bahasa Indonesia dengan Model Pembelajaran Project Base Learning (PjBL) (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze an Indonesian language teaching module for eighth-grade junior high school students designed using the Project-Based Learning (PjBL) model. The analysis focuses on the module's structure, the formulation of learning objectives, the steps in learning activities, the roles of teachers and students, and the evaluation methods implemented in the module. The research method used was descriptive qualitative, with the primary data source being an Indonesian language teaching module developed and implemented by students in the Master's Program in Indonesian Language and Literature Education. Data collection was conducted through documentation studies, while data analysis was conducted by assessing the module's alignment with the principles of PjBL and the Independent Curriculum. The results indicate that the teaching module has been systematically developed and reflects the main characteristics of PjBL, such as problem-based learning, active student involvement, collaborative work, and reflection on learning outcomes. Furthermore, this teaching module fosters the development of critical thinking skills, creativity, and student responsibility for learning. The module also aligns with efforts to strengthen the Pancasila Student Profile and supports the implementation of contextual and student-centered learning in accordance with the requirements of the Independent Curriculum.